2010
DOI: 10.1016/j.virol.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Viral pathogenesis in mice is similar for West Nile virus derived from mosquito and mammalian cells

Abstract: West Nile virus (WNV) is a mosquito-borne pathogen. During replication, WNV acquires different carbohydrates and lipid membranes, depending on its mosquito or vertebrate hosts. Consequently, WNV derived from mosquito and vertebrate cell lines differ in their infectivity for dendritic cells (DCs) and induction of type I interferon (IFN-α/β) in vitro. We evaluated the pathogenesis of WNV derived from mosquito (WNVC6/36) and vertebrate (WNVBHK) cell lines in mice. The tissue tropism, infectivity, clinical disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Interestingly, studies with cell culture have suggested that flavivirus propagated in mosquito cells could differentially modulate innate immune responses from virus grown in mammalian cells (2,40). However, this conclusion was not supported by pathogenesis studies with mice (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies with cell culture have suggested that flavivirus propagated in mosquito cells could differentially modulate innate immune responses from virus grown in mammalian cells (2,40). However, this conclusion was not supported by pathogenesis studies with mice (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Virus was produced from a full-length cDNA clone of a WNV isolate obtained from New York, NY, in 2000 (25). RNA was transcribed in vitro from the cDNA clone and electroporated into BHK-21 or C6/36 cells as previously described (14). The viral stocks were designated WNV-BHK for virus harvested from BHK-21 cells and WNV-C6/36 for virus harvested from C6/36 cells.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore determined whether spot feeding lowers the infectious dose of WNV by enhancing early infection. The ID 50 of needle-inoculated WNV in our mouse model is approximately 1 PFU (14). Thus, we inoculated 1 or 10 PFU of WNV with and without spot feeding.…”
Section: Vol 85 2011 Mosquito Saliva Enhances West Nile Virus Infecmentioning
confidence: 99%
“…Functional type I IFN in sera was measured as described previously (22). Briefly, serum samples and standards (recombinant mouse IFN-␤; Chemicon International, Temecula, CA) were diluted in complete medium, treated with 2 N HCl, and incubated at 4°C overnight.…”
Section: Cellsmentioning
confidence: 99%